Postcolonial multiculturalism in K.S.Maniam’s in a far country - Mohd Kasim, Ain Fatihah; Mani, Manimangai (Center for Resource, Research and Publication Services, 2018)
Multiculturalism can be understood as a colonial legacy, left by the incursion of the Western power in Malaya. Contributing to the cultural diversity of Malaya, colonization changed Malaya into a multicultural country. This paper explores a novel by K.S. Maniam entitled In a Far Country to see how the author depicted multiculturalism in the pre-colonial Malaya through the characters. To live in a multicultural society requires one to embrace the diversity and instill acceptance and respectfulness to those from other cultures. Maniam’s characters in attempt to do so became entangled in cultural conflicts.This article explores how the characters that were falsely promised better lives by colonization come into terms living in Malaya. The characters will be examined in terms of their attempts at assimilation in the host country and the challenges they faced in doing so. The characters’ ability and inability to embrace diversity and other cultures will also be examined. The rationale is that by understanding the characters in their endeavors, the process of assimilation and the challenges that occurred along the way can be understood. Hence, Maniam’s work can serve to show the challenges juxtaposed against the process of assimilation in shaping Malaya into a multicultural country.